Characteristics of elite cricket fast bowlers who do and do not sustain a lumbar bone stress injury: Multifactorial analysis over 4 years - Lucente, A.; Saw, A.; Sims, K.; Saw, R.; Kountouris, A.; Crowther, R. (The Journal of Sport and Exercise Science, 2022)
Lumbar bone stress injuries (LBSI) are the highest time-loss injuries among elite adult andadolescent male cricket fast bowlers. Previous research in these cohorts has not identified any consistent stand-alone risk factors beyond younger age. The purpose of this study was to address gaps in existing research by retrospectively reviewing four-seasons of data from male and female fast bowlers across multiple domains. Data of elite male and female fast bowlers was retrieved from Cricket Australia`s online database for the seasons 2016-17 to 2019-20. Bowlers who sustained a LBSI during a season, denoted `injured` (n = 43: 33 male, 10 female) were compared to bowlers who did not sustain a LBSI in the previous four years, denoted `non-injured` (n = 28: 18 male, 10 female). Musculoskeletal screening, bowling technique, and bowling frequency were compared between injured and non-injured bowlers using univariate and multivariate analyses. History of any LBSI previously (odds ratio 8.84 [1.08-37.59], p = 0.003), younger age (odds ratio 0.73 [0.61-0.86], p > 0.001), and more days bowled in the previous four weeks (1.19 [1.03-1.38], p = 0.018) explained 45% of LBSI risk in elite fast bowlers. The remaining 55% was not explained by any individual, musculoskeletal, or technique variables across all bowlers. Practitioners should take into consideration any history of LBSI and the age of the bowler when prescribing bowling frequency to reduce the risk of LBSI. An individualised and adaptive approach to fast bowler preparation may also address other factors such as musculoskeletal characteristics or bowling technique if deemed relevant to the individual at the time.